L’épiderme des statues grecques : quand le marbre se fait chair - Adeline Grand-Clément (Images Re-Vues)
In Ancient Greece, the word for the skin, khrôs, meant also « colour ». The human skin was therefore strongly connected to the notion of chromatism. The skill of a painter was evaluated through his capacity to render the subtle shades of colour-skin (andreikelon) and his ability to create the illusion of life. We are now aware of the fact that even the statues were given a colourful appearance, but unfortunately we don’t know very well what kind of treatment was reserved to the nude parts of the human body. This paper deals with the relationship between skin and colour, by focussing on one specific material: marble. Actually, it seems that this crystalline rock has been one of the favourite ground for polychromy, since the Archaic period, and we will reflect upon the reason why it was so appreciated by sculptors and painters.